VISUALISASI DATA KEBENCANAAN KABUPATEN JEPARA MENGGUNAKAN MICROSOFT POWER BI - Haris Syaifullah, Muhammad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The Jepara Regency Disaster Management Agency (BPBD) is a non-departmental government entity that is directly under the coordination of the Central National Disaster Management Agency (BNPB). One of the authorities of the Jepara Regency BPBD is to collect information related to disasters that occur in each Regency/City in the Jepara Regency area. However, until now, the annual report regarding this disaster has not been published, resulting in reduced knowledge of the people of South Sumatra regarding locations that are vulnerable to disasters in each region. This research aims to create a visualization in the form of an informative dashboard using the Microsoft Power BI platform, which is based on data regarding disaster-prone areas in Jepara Regency Province, with a focus on each sub-district/village. The visualization results show that Keling District is an area that frequently experiences landslides.